Corporate Investment Criteria and the Valuation of Risk Assets - Litzenberger, Robert H.; Budd, Alan P. (Journal of Financial and Quantitative Analysis, 1970)
A normative theory of capital budgeting requires determination of the correct cost of capital for the evaluation and selection of risky investment projects. Since different uses of funds within the firm may involve different degrees of uncertainty, the normative theory should take into account the effects of changes in the composition of the firm's portfolio of productive assets on its market valuation. The normative theory must therefore be based on a positive theory of market valuation. The objective of this paper is to develop and test an empirical specification of the positive theory.